Thermally Activated Delayed Fluorescence Materials Based on Homoconjugation Effect of Donor–Acceptor Triptycenes - Kawasumi, Katsuaki; Wu, Tony; Zhu, Tianyu; Chae, Hyun Sik; Van Voorhis, Troy; Baldo, Marc A; Swager, Timothy M (Journal of the American Chemical Society, 2015)
Donor–acceptor triptycences, TPA-QNX(CN)2 and TPA-PRZ(CN)2, were synthesized and their emissive properties were studied. They exhibited a blue-green fluorescence with emission lifetimes on the order of a microsecond in cyclohexane at room temperature. The long lifetime emission is quenched by O2 and is attributed to thermally activated delayed florescence (TADF). Unimolecular TADF is made possible by the separation and weak coupling due to homoconjugation of the HOMO and LUMO on different arms of the three-dimensional donor–acceptor triptycene. Organic light emitting devices (OLEDs) were fabricated using TPA-QNX(CN)2 and TPA-PRZ(CN)2 as emitters which displayed electroluminescence with efficiencies as high as 9.4% EQE.